2020
DOI: 10.20448/journal.512.2020.71.28.37
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Nutritional and Proximate Composition of Rain Tree (Samanea saman) Pod Samples

Abstract: The anti-nutritional and proximate composition of pods of Samanea saman were determined. About 600g of wholesome, cleaned and dried pods were divided into two portions: one portion was ground as whole pod meal while the other portion was deseeded and ground as seedless meal. The removed seeds were ground separately as a sample to obtain three samples namely: whole pod, pulp and seed samples. Triplicate data obtained were subjected to One-Way ANOVA using SPSS software of version 21. Mean values and Fisher's lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 16 publications
0
5
0
7
Order By: Relevance
“…Two gramme-portions of each flour blend samples were weighed into previously weighed dry crucibles. The crucibles with samples were dried in an oven at 105 o C, cooled in desiccators for ten minutes, reweighed and returned into the oven until a constant weight was attained [25][26][27]. The moisture content of the flour samples was calculated with the equation 1:…”
Section: Determination Of Proximate Composition Of Flour Blends Determentioning
confidence: 99%
See 3 more Smart Citations
“…Two gramme-portions of each flour blend samples were weighed into previously weighed dry crucibles. The crucibles with samples were dried in an oven at 105 o C, cooled in desiccators for ten minutes, reweighed and returned into the oven until a constant weight was attained [25][26][27]. The moisture content of the flour samples was calculated with the equation 1:…”
Section: Determination Of Proximate Composition Of Flour Blends Determentioning
confidence: 99%
“…The Ash content was determined following the AOAC [24] method as modified by Uzoukwu et al [27]. Two grams of the samples were weighed in triplicate into previously weighed silica crucibles.…”
Section: Determination Of Ash Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…The matured pods are black-brown, oblong, lumpy filled with a sticky, brownish pulp that is sweet and edible with aroma which attracts animals like cows when ripened and fallen. [3] reported that the pods are rich in proteins and carbohydrates and as such can be utilized as nutrient supplements in feeds. The sugary pulp must have contributed to the high carbohydrate content of the pod which also produced Samanea saman wine with above 9% alcohol content [1].…”
Section: Introductionmentioning
confidence: 99%